Health Improvements Impact Income Inequality - Rainer Franz Kotschy (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper investigates whether and to what extent long-run trends in population health affected income inequality in the United States over the period 1960-2000. To isolate exogenous variation in health over time, the analysis exploits the sharp decline in cardiovascular disease mortality across states that originated from medical advances in the treatment and prevention of these diseases after 1960. The results demonstrate that health improvements contributed to rising income inequality through mechanisms related to education.
Keywords: I14; I24; J11; 330; population health; aging; Gini coefficient; skill-biased technical change